PENGARUH PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING TERHADAP KEMAMPUAN BERPIKIR ANALISIS SISWA PADA KONSEP EKOSISTEM DI KELAS X SMA NEGERI 1 CILIMUS KABUPATEN KUNINGAN - Agustia, Dita Hasti; Dirdjosoemarto, Soendjojo; Nurlaelah, Ilah (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2016)
The background of the research is student’s analytical thinking in biology class still low. That showed by student difficulty to identified and formulated the problem, unknown to separated and connected some parts of problem, and difficulty to make summarize based on relevant data and facts. The research question is how the influence by using of active knowledge sharing strategy to student’s analytical thinking skill on the ecosystem concept at tenth grade of SMA Negeri 1 Cilimus Kuningan Regency? The research purposed is to know the influence by using of active knowledge sharing strategy to student’s analytical thinking skill on the ecosystem concept at tenth grade of SMA Negeri 1 Cilimus Kuningan Regency. The method used in the research is experimental design. The population of the research is all of students at tenth grade of SMA Negeri 1 Cilimus academic years 2012/2013 about eight classes they are 256 students. The sampling technique with cluster random sampling, so the writer choose sample randomly and get class X.8 with 35 students. The technique of data processing used is normality test and hypothesis test (z test). The normality test does to know the normality of data and the result is ² hit (6,450) ² daf (11,07), so the data is distributed normally. The hypothesis test does to know the influence by using of active knowledge sharing strategy to student’s analytical thinking skill on the ecosystem concept at tenth grade of SMA Negeri 1 Cilimus Kuningan Regency. Based on the statistical accounting the result is z hit (5,702) z daf (1,65), so Hi is accepted means that they are the influence by using of active knowledge sharing strategy to student’s analytical thinking skill on the ecosystem concept at tenth grade of SMA Negeri 1 Cilimus Kuningan Regency. Based on the analytical result of postest data, using of active knowledge sharing strategy can improve student’s analytical thinking skill on the ecosystem concept, it showed by the postest value get average 83,057 and analytical data of assesmen include to good category.Key words: active knowledge sharing strategy, analytical thinking skill